Corrigendum: Bobinac M, Šušić N, Šijačić-Nikolić M, Kerkez Janković I, Veljović-Jovanović S., Photosynthetic insights into winter-green leaves in Quercus pubescens Willd. seedlings, Arch Biol Sci. 2024;76(2):223-32 - Editoral (Archives of Biological Sciences)
The authors of the article: Bobinac M, Šušić N, Šijačić-Nikolić M, Kerkez Janković I, Veljović-Jovanović S. Photosynthetic insights into winter-green leaves in Quercus pubescens Willd. seedlings. Arch Biol Sci. 2024;76(2):223-32. have notified the Editorial Office of an error in the Funding section. The name “Ministry of Education, Science and Technological Development of the Republic of Serbia” was incorrectly stated and should instead read “Ministry of Science, Technological Development and Innovation of the Republic of Serbia.” The authors have requested this correction, and as a result, the journal is publishing this Corrigendum. The correct funding source is: This research was funded by the Ministry of Science, Technological Development and Innovation of the Republic of Serbia, Contracts 451-03-66/2024-03/200053 and 451-03-65/2024-03/200169, and by the Secretariat for Environmental Protection of the City of Belgrade, Project: Identification and Monitoring of the Gene Pool of Rare, Vulnerable, and Endangered Plant Species in NM Kosutnjak Forest. Link to the corrected article 10.2298/ABS240417015B